Ultraviolet-cured acrylate pressure-sensitive adhesive with adjustable adhesion performance as well as preparation method and application of ultraviolet-cured acrylate pressure-sensitive adhesive
By introducing hydrogen-grafted crosslinking photoinitiator and multifunctional crosslinking agent into ultraviolet cured hot melt pressure sensitive adhesive, a crosslinking network structure is solved, and the lack of cohesion intensity and poor performance of photoinitiator in the prior art are solved. The problem is that high cohesive strength and adjustable adhesion performance are achieved.
Patent Information
- Application Number
- CN202411830740.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-14
AI Technical Summary
The existing ultraviolet cured hot melt pressure-sensitive adhesives have shortcomings in cohesion strength and bonding properties, and small-molecular photoinitiators have problems such as mobility, unstable reaction rate, high toxicity and poor thermal stability, making it difficult to adjust the mechanical strength .
A hydrogen-grabbing crosslinking photoinitiator and a multifunctional crosslinking agent are introduced to form a photosensitive prepolymer through free radical polymerization. After coating, it is irradiated with ultraviolet light to form a crosslinked network structure, which improves cohesion intensity and adjusts adhesion performance.
Improve the cohesive strength and shear strength of pressure-sensitive adhesives, reduce the migration of photoinitiators, enhance the anti-interference ability to oxygen, realize the adjustable adhesion performance, and solve the residual glue and glue on the base surface of the adhesive Transfer issue.
Smart Images

Figure BDA0005185489600000081
Abstract
Description
Technical Field
[0001] The invention belongs to the field of adhesives, and in particular relates to an acrylate pressure-sensitive adhesive with ultraviolet curing and adjustable adhesion properties, and a preparation method and application thereof. Background Art
[0002] Pressure-sensitive adhesive (PSA) is a non-metallic material that relies on adhesion and cohesion to bond materials together. In recent years, it has been widely used in many fields such as self-adhesive tapes, labels, protective films, logo films and medical products. Among them, acrylic pressure-sensitive adhesives account for about 40% of the market share, and are mainly solvent-based (50%), water-based (40%) and photoinitiator solvent-free systems (about 10%), among which the solvent-free type shows an increasing trend year by year. In particular, UV-curable hot-melt pressure-sensitive adhesives have a high viscosity of more than 100 Pas at room temperature and almost no fluidity, so they need to be heated to 120-150°C to achieve fluidity suitable for coating. After coating, they are irradiated with UV lamps to achieve cross-linking, thereby obtaining the desired adhesive properties.
[0003] Photoinitiators play a key role in UV-curable acrylic hot-melt pressure-sensitive adhesives, and their chemical properties and dosage directly affect the reaction effect. However, existing small molecule photoinitiators have many disadvantages, including large mobility, narrow light absorption range, instability of reaction rate (significantly affected by oxygen inhibition), potential high toxicity and poor thermal stability. In addition, current UV hot-melt pressure-sensitive adhesives perform poorly in terms of cohesive strength, often have problems such as residual adhesive on the adhesive base surface and difficulty in peeling, and are prone to adhesive transfer after prolonged use.
[0004] In view of this situation, although the small molecule photoinitiators in the patent applications with publication numbers CN117402561A, CN106459302B and US9475968 are widely used in UV-curable hot melt pressure-sensitive adhesives, they also face performance limitations. At the same time, the UV-curable hot melt pressure-sensitive adhesives mentioned in the patent applications with publication numbers CN107699172A and CN118421230A have a fixed peel strength. If the mechanical strength needs to be adjusted, the original formula needs to be changed or adjusted by adding tackifiers, resulting in a decrease in the complexity and tolerance of the formula. These problems urgently need to be solved through molecular structure design optimization to improve the performance and application range of UV hot melt pressure-sensitive adhesives. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies in the above-mentioned prior art, the primary purpose of the present invention is to provide a method for preparing a UV-curable acrylate pressure-sensitive adhesive with adjustable adhesion properties; while maintaining the advantages of the existing UV-curing technology, the method introduces a hydrogen-abstracting cross-linking photoinitiator and a multi-functional cross-linking agent, forms a photosensitive prepolymer through free radical polymerization, and forms a cross-linked network structure after coating and UV irradiation, thereby improving the cohesive strength of the pressure-sensitive adhesive, avoiding the migration of the photoinitiator, and increasing the anti-interference ability to oxygen, thereby improving the product performance of the UV-curable hot-melt pressure-sensitive adhesive.
[0006] Another object of the present invention is to provide a UV-curable acrylate pressure-sensitive adhesive with adjustable adhesion properties prepared by the above preparation method.
[0007] Another object of the present invention is to provide an application of the above-mentioned UV-curable acrylate pressure-sensitive adhesive with adjustable adhesion properties.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A method for preparing a UV-curable acrylic pressure-sensitive adhesive with adjustable adhesion properties comprises the following steps:
[0010] (1) mixing acrylate adhesive monomers, acrylate cohesive monomers, acrylate modified functional monomers, photoinitiators, chain transfer agents, free radical thermal initiators, branched crosslinking agents, and organic solvents to form a mixed solution, heating the solution to 65 to 90° C. for free radical polymerization, then keeping the solution at 75 to 90° C. for reaction, and then performing reduced pressure distillation at 120 to 160° C. to obtain a solvent-free acrylate copolymer;
[0011] (2) coating the solvent-free acrylate copolymer obtained in step (1) on a substrate at a temperature of 100 to 140° C., and then irradiating the substrate with ultraviolet light to obtain an ultraviolet-curable acrylate pressure-sensitive adhesive with adjustable adhesion properties;
[0012] The photoinitiator in step (1) is one or a mixture of 4-acryloxy-2-hydroxybenzophenone, 4-acryloxybenzophenone, 4-acryloxyethoxybenzophenone, 4-acryloxybutoxybenzophenone and 4-acryloxyhexyloxybenzophenone;
[0013] The branched crosslinking agent in step (1) is a branched polymer generated by reaction of a multifunctional monomer, preferably one or a mixture of ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, di(trimethylolpropane) tetraacrylate, and pentaerythritol tetraacrylate.
[0014] The preparation method of the solvent-free acrylate copolymer in step (1) is specifically as follows:
[0015] 100 parts by weight of monomers, 0.5-1.5 parts by weight of photoinitiators, 0.6-1.5 parts by weight of chain transfer agents, 0.3-1.5 parts by weight of free radical thermal initiators, 1.0-3.5 parts by weight of branched crosslinking agents and 70-100 parts by weight of organic solvents are uniformly mixed to obtain a mixed solution, wherein the monomers include 70-85 parts by weight of acrylate viscosity monomers, 5-15 parts by weight of acrylate cohesive monomers and 3-15 parts by weight of acrylate modified functional monomers; 10-25 wt % of the mixed solution obtained above is taken as a base material, heated to 65-90° C. for free radical initiated polymerization reaction, and the remaining mixed solution is dripped at a uniform speed, maintained at 75-90° C. for reaction for 1-2 hours to obtain an acrylate polymer solution; the acrylate polymer solution is subjected to reduced pressure distillation at a temperature of 120-160° C. to remove the organic solvent to obtain a solvent-free acrylate copolymer.
[0016] The acrylic ester adhesive monomer is an acrylic ester monomer with a glass transition temperature of -75 to -10°C, including one or a mixture of isooctyl acrylate, butyl acrylate, ethyl acrylate, 2-ethoxyethyl acrylate and 2-ethylhexyl acrylate;
[0017] The acrylic acid ester comonomer is one or a mixture of methyl acrylate, methyl methacrylate, vinyl acetate, 2-phenoxyethyl acrylate and benzyl acrylate;
[0018] The acrylic ester modified functional monomer is one or a mixture of hydroxyethyl acrylate, hydroxyethyl methacrylate, acrylic acid, methacrylic acid and hydroxypropyl methacrylate.
[0019] The chain transfer agent is one or a mixture of n-dodecyl mercaptan, 2,2′-(1,2-ethylenedioxy)diethyl mercaptan and tert-dodecyl mercaptan.
[0020] The free radical thermal initiator is one or a mixture of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate and diethyl azobisisobutyrate.
[0021] The organic solvent is ethyl acetate, toluene or xylene.
[0022] The coated substrate in step (2) is PET film, BOPP film, paper or non-woven fabric, and the coating amount is 10 to 60 g / m 2 .
[0023] The ultraviolet light source described in step (2) is an ultraviolet lamp with a wavelength of 240 to 400 nm.
[0024] A UV-curable acrylic pressure-sensitive adhesive with adjustable adhesion properties prepared by the above-mentioned preparation method.
[0025] The above-mentioned UV-curable acrylate pressure-sensitive adhesive with adjustable adhesion properties is used in pressure-sensitive adhesive products. By adjusting the UV light irradiation energy to adjust the crosslinking density, the adhesion properties of the pressure-sensitive adhesive are adjusted to obtain pressure-sensitive adhesive products with different adhesion properties.
[0026] The pressure-sensitive adhesive products include pressure-sensitive adhesive tapes, labels and medical products.
[0027] Compared with the prior art, the present invention has the following technical effects:
[0028] (1) The multifunctional cross-linking agent introduced in the present invention can increase the branching degree of polymer molecules, thereby increasing the cross-linking degree and enhancing the cohesive strength; moderate cross-linking can improve the adhesion performance, making the bond between the adhesive and the substrate more firm, and there is no adhesive residue or adhesive transfer when the substrate is adhered for a long time, and it is easy to peel off;
[0029] 2) The present invention introduces a polymerizable photoinitiator, which is introduced into the molecular chain through a free radical polymerization reaction. It has high reactivity and low mobility, which helps to improve the shear strength of the pressure-sensitive adhesive and reduce toxicity. This type of photoinitiator has good solubility and high temperature tolerance, and after UV radiation, the photolytic fragments that do not produce a strong odor migrate to the surface of the hot-melt pressure-sensitive adhesive.
[0030] 3) The UV-curable acrylate pressure-sensitive adhesive with adjustable adhesion properties designed by the present invention can adjust the adhesion properties by adjusting the light curing energy, which solves the problem of adjusting the product formula in the application link and increases the adaptability of the product.
[0031] In general, the UV-curable acrylate pressure-sensitive adhesive with adjustable adhesion provided by the present invention combines the economic benefits of hot-melt coating technology with the excellent properties of acrylate chemistry, including excellent aging tolerance, optical transparency and heat resistance, bringing more application possibilities and technological breakthroughs to the industry. In addition, the material is solvent-free, non-toxic and odorless, has a fast curing speed, adjustable mechanical properties, and has an anti-oxidation and polymerization inhibition effect (insensitive to oxygen), and is widely used in the production of pressure-sensitive tapes, labels and medical products. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Experimental methods without specific conditions in the examples are carried out according to conventional methods and conditions.
[0033] Method for determining initial adhesion: The loop initial adhesion test of PET pressure-sensitive tape is tested in accordance with GB / T 31125-2014.
[0034] Method for determining peel strength: The peel strength of PET pressure-sensitive tape is tested using a tensile testing machine in accordance with GB / T2792-2014.
[0035] Method for determining the holding adhesiveness: The holding adhesiveness of PET pressure-sensitive tape is tested in accordance with GB / T4851-2014.
[0036] Embodiment 1:
[0037] (1) 50 g of isooctyl acrylate, 25 g of butyl acrylate, 7.5 g of acrylic acid, 10 g of vinyl acetate, 7.5 g of 2-phenoxyethyl acrylate, 0.6 g of n-dodecyl mercaptan, 1.0 g of 4-acryloyloxyethoxybenzophenone, 0.5 g of azobisisobutyronitrile, 1.5 g of ethoxylated trimethylolpropane triacrylate, and 100 g of ethyl acetate were mixed to form 203.6 g of a mixed solution. Then 40 g of the mixed solution was taken out as a base material and placed in a 500 ml four-necked flask equipped with a cooling reflux, dropwise addition device, a thermometer, and a mechanical stirring device (100 rpm). The mixture was heated to 75° C. to carry out a free radical initiated polymerization reaction. After the reaction was initiated, the reaction released heat. The solution temperature was maintained at 80° C., and the remaining mixed solution was slowly added dropwise to continue the reaction. After the addition was completed, the mixture was kept at 80° C. for 2 h to obtain an acrylate polymer solution. The organic solvent was then removed by reduced pressure distillation at 140° C. to obtain a solvent-free acrylate copolymer.
[0038] (2) According to the coating amount of 20 g / m 2 The solvent-free acrylate copolymer obtained in step (1) was melted at 120°C and coated on a PET film, and then photocured with an ultraviolet light source (240-400 nm). Different photocuring energies were controlled to obtain an adhesive tape of an acrylate pressure-sensitive adhesive with adjustable adhesion properties, which was marked as Y-1 adhesive. The performance test was carried out according to the relevant test method, and the results are shown in Table 1.
[0039] Embodiment 2:
[0040] (1) 55 g of isooctyl acrylate, 25 g of butyl acrylate, 7.5 g of acrylic acid, 5 g of methyl methacrylate, 7.5 g of benzyl acrylate, 1.0 g of n-dodecyl mercaptan, 0.8 g of 4-acryloxybenzophenone, 0.8 g of azobisisobutyronitrile, 2.0 g of trimethylolpropane triacrylate and 80 g of xylene were mixed to form 184.6 g of a mixed solution. Then 37 g of the mixed solution was taken out as a base material and placed in a 500 ml four-necked flask equipped with a cooling reflux, dripping, thermometer and mechanical stirring device (80 rpm). The mixture was heated to 85° C. for free radical initiated polymerization. After the reaction was initiated, the reaction released heat. The solution temperature was maintained at 85° C., and the remaining mixed solution was slowly dripped to continue the reaction. After the dripping was completed, the temperature was raised to 90° C. and the mixture was kept warm for 1.5 hours to obtain an acrylate polymer solution. The organic solvent was then removed by reduced pressure distillation at 135° C. to obtain a solvent-free acrylate copolymer.
[0041] (2) According to the coating amount of 20 g / m 2 The solvent-free acrylate copolymer obtained in step (1) was melted at 110°C and coated on a PET film, and then photocured with an ultraviolet light source (240-400nm). By controlling different photocuring energies, an adhesive tape of an acrylate pressure-sensitive adhesive with adjustable adhesion properties was obtained, which was marked as Y-2 adhesive. The performance test was carried out according to the relevant test method, and the results are shown in Table 1.
[0042] Embodiment 3:
[0043] (1) 55 g of 2-ethylhexyl acrylate, 30 g of ethyl acrylate, 4.5 g of hydroxyethyl acrylate, 5 g of methyl acrylate, 5.5 g of 2-phenoxyethyl acrylate, 1.2 g of tert-dodecyl mercaptan, 1.0 g of 4-acryloxybutoxybenzophenone, 0.7 g of azobisisoheptanenitrile, 2.0 g of propoxylated trimethylolpropane triacrylate, and 100 g of ethyl acetate were mixed to form 194.6 g of a mixed solution. Then, 35 g of the mixed solution was taken out as a base material and placed in a 500 ml four-necked flask equipped with a cooling reflux, dripping, thermometer and mechanical stirring device (80 rpm). The mixture was heated to 75° C. for free radical initiated polymerization. After the reaction was initiated, the reaction released heat. The solution temperature was maintained at 75° C., and the remaining mixed solution was dripped slowly at a uniform speed to continue the reaction. After the dripping was completed, the temperature was raised to 80° C. and the mixture was kept warm for 1 hour to obtain an acrylate polymer solution. The organic solvent was then removed by reduced pressure distillation at 135° C. to obtain a solvent-free acrylate copolymer.
[0044] (2) According to the coating amount of 20 g / m 2The solvent-free acrylate copolymer obtained in step (1) was melted at 130°C and coated on a PET film, and then photocured with an ultraviolet light source (240-400nm). The photocuring energy was controlled to obtain an adhesive tape of an acrylate pressure-sensitive adhesive with adjustable adhesion properties, which was marked as Y-3 adhesive. The performance test was carried out according to the relevant test method, and the results are shown in Table 1.
[0045] Embodiment 4:
[0046] (1) 45 g of 2-ethylhexyl acrylate, 30 g of butyl acrylate, 7.5 g of hydroxypropyl methacrylate, 10 g of methyl methacrylate, 7.5 g of vinyl acetate, 1.5 g of tert-dodecyl mercaptan, 1.5 g of 4-acryloxybutoxybenzophenone, 1.0 g of diethyl azobisisobutyrate, 2.5 g of ethoxylated trimethylolpropane triacrylate, and 90 g of ethyl acetate were mixed to form 196.5 g of a mixed solution. Then, 35 g of the mixed solution was taken out as a base material and placed in a 500 ml four-necked flask equipped with a cooling reflux, dripping, thermometer and mechanical stirring device (70 rpm). The mixture was heated to 78° C. for free radical initiated polymerization. After the reaction was initiated, the reaction released heat. The solution temperature was maintained at 80° C., and the remaining mixed solution was dripped slowly at a uniform speed to continue the reaction. After the dripping was completed, the temperature was raised to 85° C. and the mixture was kept warm for 1.5 h to obtain an acrylate polymer solution. The organic solvent was then removed by reduced pressure distillation at 150° C. to obtain a solvent-free acrylate copolymer.
[0047] (2) According to the coating amount of 20 g / m 2 The solvent-free acrylate copolymer obtained in step (1) was melted at 130°C and coated on a PET film, and then photocured with an ultraviolet light source (240-400nm), and different curing time and photocuring energy were controlled to obtain an adhesive tape of an acrylate pressure-sensitive adhesive with adjustable adhesion performance, which was marked as Y-4 adhesive. The performance test was carried out according to the relevant test method, and the results are shown in Table 1.
[0048] Embodiment 5:
[0049] (1) 55 g of 2-ethylhexyl acrylate, 25 g of butyl acrylate, 7.5 g of methacrylic acid, 5 g of methyl methacrylate, 7.5 g of vinyl acetate, 1.3 g of tert-dodecyl mercaptan, 1.3 g of 4-acryloxybenzophenone, 1.5 g of azobisisobutyronitrile, 3.5 g of trimethylolpropane triacrylate, and 90 g of ethyl acetate were mixed to form 197.6 g of a mixed solution. Then, 35 g of the mixed solution was taken out as a base material and placed in a 500 ml four-necked flask equipped with a cooling reflux, dripping, thermometer and mechanical stirring device (80 rpm). The mixture was heated to 85° C. for free radical initiated polymerization. After the reaction was initiated, the reaction released heat. The solution temperature was maintained at 70° C., and the remaining mixed solution was dripped slowly at a uniform speed to continue the reaction. After the dripping was completed, the temperature was raised to 75° C. and the mixture was kept warm for 1.5 h to obtain an acrylate polymer solution. The organic solvent was then removed by reduced pressure distillation at 150° C. to obtain a solvent-free acrylate copolymer.
[0050] (2) According to the coating amount of 20 g / m 2 The solvent-free acrylate copolymer obtained in step (1) was melted at 130°C and coated on a PET film, and then photocured with an ultraviolet light source (240-400nm). Different photocuring energies were controlled to obtain an adhesive tape of an acrylate pressure-sensitive adhesive with adjustable adhesion properties, which was marked as Y-5 adhesive. The performance test was carried out according to the relevant test method, and the results are shown in Table 1.
[0051] Table 1: Performance test results of pressure-sensitive adhesive tape examples (25°C)
[0052]
[0053] According to the classification of adhesion performance in the pressure-sensitive adhesive industry (180° peel strength), high-quality permanent adhesive is >14N / 25mm, permanent adhesive (10-14N / 25mm), semi-detachable adhesive (6-8N / 25mm), and detachable and repositionable adhesive (2-4N / 25mm). The test results of the embodiment show that the adhesion performance of the sample can be adjusted according to the change of light curing intensity, which significantly improves its application range in the industrial field and the adaptability of the product. These results are mainly due to the molecular structure design of the sample. By increasing the light intensity, the cross-linking degree of the pressure-sensitive adhesive is adjusted, and then the cohesive strength changes, so that the peel strength and initial viscosity can be controlled and adjusted, and the sustained adhesion test is still more than 168h, and there is no obvious whitening change after soaking in water for 24h. The present invention provides new ideas and possibilities for the application of pressure-sensitive adhesives.
[0054] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a UV-curable acrylic pressure-sensitive adhesive with adjustable adhesion properties, characterized in that The steps include: (1) mixing acrylate adhesive monomers, acrylate cohesive monomers, acrylate modified functional monomers, photoinitiators, chain transfer agents, free radical thermal initiators, branched crosslinking agents, and organic solvents to form a mixed solution, heating the solution to 65 to 90° C. for free radical polymerization, then keeping the solution at 75 to 90° C. for reaction, and then performing reduced pressure distillation at 120 to 160° C. to obtain a solvent-free acrylate copolymer; (2) coating the solvent-free acrylate copolymer obtained in step (1) on a substrate at a temperature of 100 to 140° C., and irradiating the substrate with ultraviolet light to obtain a UV-curable solvent-free acrylate pressure-sensitive adhesive; The photoinitiator in step (1) is one or a mixture of 4-acryloxy-2-hydroxybenzophenone, 4-acryloxybenzophenone, 4-acryloxyethoxybenzophenone, 4-acryloxybutoxybenzophenone and 4-acryloxyhexyloxybenzophenone; The branched crosslinking agent in step (1) is a branched polymer generated by reaction of multifunctional monomers, specifically including one or a mixture of ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, di(trimethylolpropane) tetraacrylate, and pentaerythritol tetraacrylate.
2. The preparation method according to claim 1, characterized in that: The preparation method of the solvent-free acrylate copolymer in step (1) is specifically as follows: 100 parts by weight of monomers, 0.5-1.5 parts by weight of photoinitiators, 0.6-1.5 parts by weight of chain transfer agents, 0.3-1.5 parts by weight of free radical thermal initiators, 1.0-3.5 parts by weight of branched crosslinking agents and 70-100 parts by weight of organic solvents are uniformly mixed to obtain a mixed solution, wherein the monomers include 70-85 parts by weight of acrylate viscosity monomers, 5-15 parts by weight of acrylate cohesive monomers and 3-15 parts by weight of acrylate modified functional monomers; 10-25 wt % of the mixed solution obtained above is taken as a base material, heated to 65-90° C. for free radical initiated polymerization reaction, and the remaining mixed solution is dripped at a uniform speed, maintained at 75-90° C. for reaction for 1-2 hours to obtain an acrylate polymer solution; the acrylate polymer solution is subjected to reduced pressure distillation at a temperature of 120-160° C. to remove the organic solvent to obtain a solvent-free acrylate copolymer.
3. The preparation method according to claim 1 or 2, characterized in that: The acrylic ester adhesive monomer is an acrylic ester monomer with a glass transition temperature of -75 to -10°C, including one or a mixture of isooctyl acrylate, butyl acrylate, ethyl acrylate, 2-ethoxyethyl acrylate and 2-ethylhexyl acrylate; The acrylic acid ester comonomer is one or a mixture of methyl acrylate, methyl methacrylate, vinyl acetate, 2-phenoxyethyl acrylate and benzyl acrylate; The acrylic acid ester modified functional monomer is one or a mixture of hydroxyethyl acrylate, hydroxyethyl methacrylate, acrylic acid, methacrylic acid and hydroxypropyl methacrylate.
4. The preparation method according to claim 1 or 2, characterized in that: The chain transfer agent is one or a mixture of n-dodecyl mercaptan, 2,2′-(1,2-ethylenedioxy)bis(ethyl mercaptan) and tert-dodecyl mercaptan; the free radical thermal initiator is one or a mixture of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate and diethyl azobisisobutyrate; and the organic solvent is ethyl acetate, toluene or xylene.
5. The preparation method according to claim 1, characterized in that: The coated substrate in step (2) is PET film, BOPP film, paper or non-woven fabric, and the coating amount is 10 to 60 g / m 2 .
6. The preparation method according to claim 1, characterized in that: The ultraviolet light source described in step (2) is an ultraviolet lamp with a wavelength of 240 to 400 nm.
7. A UV-curable acrylic pressure-sensitive adhesive with adjustable adhesion properties prepared by the preparation method according to any one of claims 1 to 6.
8. The use of the UV-curable acrylate pressure-sensitive adhesive with adjustable adhesion properties in pressure-sensitive adhesive products according to claim 7, characterized in that: The cross-linking density can be adjusted by adjusting the ultraviolet light irradiation energy, thereby adjusting the adhesion performance of the pressure-sensitive adhesive to obtain pressure-sensitive adhesive products with different adhesion performances.
9. The use according to claim 8, characterized in that: The pressure-sensitive adhesive products include pressure-sensitive adhesive tapes, labels and medical products.
Citation Information
Patent Citations
Light-cured hot-melt pressure-sensitive adhesive
CN107699172A
Photocuring hot-melt pressure-sensitive adhesive, preparation method thereof and removable label
CN117402561A
Polyacrylate UV photocuring hot-melt pressure-sensitive adhesive and preparation method thereof
CN118421230A
Ultraviolet radiation curable pressure sensitive acrylic adhesive
US9475968B2
Solvent-free ultraviolet curing pressure sensitive adhersive for polyethylene protective film and preparation method thereof
CN101649171A